1993
DOI: 10.3102/00346543063001001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anomalous Data in Knowledge Acquisition: A Theoretical Framework and Implications for Science Instruction

Abstract: Understanding how science students respond to anomalous data is essential to understanding knowledge acquisition in science classrooms. In this report, we present a detailed analysis of the ways in which scientists and science students respond to anomalous data. We postulate that there are seven distinct forms of response to anomalous data, only one of which is to accept the data and change theories. The other six responses involve discounting the data in various ways in order to protect the preinstructional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
351
1
24

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 993 publications
(408 citation statements)
references
References 132 publications
16
351
1
24
Order By: Relevance
“…For example, studies on conceptual change have shown that readers hold fast to previously acquired knowledge and beliefs even when they are presented with new and contradicting evidence (Chinn & Brewer, 1993;Vosniadou, 1994). Research on the persistence of discredited or corrected information (Anderson, Lepper, & Ross, 1980;Ross, Lepper, & Hubbard, 1975) and on the continued influence of misinformation (Johnson & Seifert, 1994) yielded similar results.…”
Section: A Two-step Model Of Processing Conflicting Information In Musupporting
confidence: 58%
“…For example, studies on conceptual change have shown that readers hold fast to previously acquired knowledge and beliefs even when they are presented with new and contradicting evidence (Chinn & Brewer, 1993;Vosniadou, 1994). Research on the persistence of discredited or corrected information (Anderson, Lepper, & Ross, 1980;Ross, Lepper, & Hubbard, 1975) and on the continued influence of misinformation (Johnson & Seifert, 1994) yielded similar results.…”
Section: A Two-step Model Of Processing Conflicting Information In Musupporting
confidence: 58%
“…Confronting students with contradictory evidence is a common and effective teaching practice in other domains where misconceptions are frequent, such as science education (e.g., Chinn & Brewer, 1993). Moreover, people with high confidence in their errors have been found to be particularly responsive to feedback contradicting their beliefs (e.g., Butterfield & Metcalfe, 2001).…”
Section: Implications For Instructionmentioning
confidence: 99%
“…Beyond the observations of Howe and her colleagues (2013), researchers have also raised the concern that cognitive conflict as a general classroom strategy overlooks the impact of developmental, motivational, or societal pressures that students face (Pintrich, Marx, & Boyle, 1993;Vosniadou, 2007), specifically that any lesson designed to generate cognitive conflict might not be meaningful to students (Chinn & Brewer, 1993Lee & Byun, 2012). To meet these challenges we felt that by creating a strong connection between scientific models and the nature of knowledge within the context of teaching and learning (as our students would face in their careers as teachers), as well as supporting the metacognitive work necessary to mediate the challenge our students faced in our course, we would address the fundamental concerns well summarized more recently by Vosniadou (2007).…”
Section: Literature Reviewmentioning
confidence: 99%